Healthy bread as an alternative to traditional bread - Rodrigues, A. (2012)
Today, bread is part of the culture and eating habits of most people and can be considered one of the most consumed foods in the world. The bread is made from a simple mixture of flour, water, salt and yeast, and it is an extremely versatile food and with a very good digestibility. Since it was first produced for thousands of years, it has undergone changes both in terms of production methods and in terms of its constitution, thus giving place nowadays to a wide variety of breads available on the market. The objectives of this study were to compare the sensory and nutritionally attributes of a special healthier bread, ―Pão São‖, which is a recent product in the Portuguese market. Nutritionally this type of bread turned out to be a food with high nutritional value, with a low salt content (0.4%, about half of traditional bread), and being a good source of omega-3 (0.67%), fibre and protein when compared with the traditional bread. These differences are mainly due to the wide variety of raw materials selected to the preparation of this bread, including the mixture of flour (wheat flour type 150 and 65 and rye flour type 70), oatmeal, sunflower and linseed seeds, soy, fish oil extracts rich in omega 3, malt and milk protein. From the results of the sensory analysis, conducted by a panel of 40 untrained tasters aged 7 to 63 years, it was found that the traditional breads from the region closest to the marketing of healthy bread were preferred by the tasters, especially for their wood and bread flavour, as well as elasticity. The healthy bread was evaluated as a denser bread, with a more intense fermented flavour. With this work it was concluded that the healthy bread is a nutritious and healthy bread, being currently recommended by the Portuguese Foundation of Cardiology. However from the sensory point of view, consumers still slighly prefer the traditional bread.